2010
DOI: 10.1177/0893318910377068
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Anticipatory Socialization (VAS): A Communicative Model of Adolescents’ Interests in STEM

Abstract: Models of career development have focused on important vocational influences such as self-efficacy, exposure, and gender prescriptions but have glossed over the role of communication in socializing adolescents toward or from various careers. We investigate academic interests in math and science and related career aspirations in science, technology, engineering, and mathematics (STEM). Drawing on data from 38 focus groups (241 students), the proposed Vocational Anticipatory Socialization (VAS) model of STEM dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 66 publications
0
88
2
Order By: Relevance
“…Although these elements of socialization may manifest prior to entry, research has yet to fully explore what constitutes socialization that occurs in anticipatory socialization. Past research has shown that prior experiences, like recruitment activities and even the messages we receive as children, socialize us into organizations and occupations (e.g., Buzzanell, Berkelaar, & Kisselburgh, 2011;Gabor, 2013;Hylmo, 2006;Levine & Hoffner, 2006;Lucas, 2011;Myers, Jahn, Gailliard, & Stoltzfus, 2011). However, we know little about how internships-a prevailing practice for most college-educated people entering the workforce today-contribute to organizational and vocational socialization.…”
Section: Study Rationalementioning
confidence: 90%
See 1 more Smart Citation
“…Although these elements of socialization may manifest prior to entry, research has yet to fully explore what constitutes socialization that occurs in anticipatory socialization. Past research has shown that prior experiences, like recruitment activities and even the messages we receive as children, socialize us into organizations and occupations (e.g., Buzzanell, Berkelaar, & Kisselburgh, 2011;Gabor, 2013;Hylmo, 2006;Levine & Hoffner, 2006;Lucas, 2011;Myers, Jahn, Gailliard, & Stoltzfus, 2011). However, we know little about how internships-a prevailing practice for most college-educated people entering the workforce today-contribute to organizational and vocational socialization.…”
Section: Study Rationalementioning
confidence: 90%
“…For example, Greenberger, Steinberg, Ruggiero (1982) studied high school students' part-time employment experiences. In addition, Myers et al (2011) explored middle and high school students' vocational anticipatory socialization to math and science. Their work demonstrated that five elements (culture/SES, gender, vocational messages, experience, and personal factors) influenced career interests in science, technology, engineering, and mathematics.…”
Section: Vocational Anticipatory Socialization Vocational Anticipatomentioning
confidence: 99%
“…In comparing the narratives of selfidentified calling and noncalling participants, this paper contends that the sources (e.g. fit, guidance from friends and family) that shape a calling, career, and job orientation are not unusual in themselves; however, the development of a calling perception is distinctive in Conversely, participants who demonstrated a greater reliance on and compliance with prescription messages (Myers et al, 2011), and who reported opting for medicine to fulfil their 'duties' to their parents, were unlikely to discuss their occupation as a calling. This is in contrast to Zhang et al's (2014) study in China, a country that also has a collectivist culture, which found that an occupational calling can be characterized by a sense of duty towards family, society and nation.…”
Section: Calling Orientations: India 23mentioning
confidence: 99%
“…In addition to the family legacy paradigm, this study draws on four prominent types of family communication that are relevant to how individuals develop an interest in educational and career pursuits (Myers et al, 2011). Based on the vocational anticipatory socialization The next section provides details of data collection and analysis, and drawing on the aforementioned theories, a presentation and discussion of the findings.…”
Section: Literature Overview Callingsmentioning
confidence: 99%
See 1 more Smart Citation